I dont understand how this can be factored!

Thank you for the opportunity to help you with your question!

m^4 - 1

= (m^2)^2 - 1^2 Hint: Write m^4 = (m^2)^2 and 1 = 1^2

= (m^2 + 1) (m^2-1) Hint: use formula a^2 - b^2 = (a+b)(a-b)

= (m^2+1)(m^2 - 1^2) Hint: use formula a^2 - b^2 = (a+b)(a-b)

=(m^2+1)(m-1)(m+1)

Hence the complete factors are (m^2+1)(m-1)(m+1)

Do you have any other question? I am going offline in sometime

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up